(untitled) (Global Journal of Human-Social Science, 2013)
This paper attempts to unveil the cultural, socio-political and socio-economic correlates of begging in cities, particularly of developing countries. With illustrations from Islamic and Christian scriptures, and examples from cities across the world, with a particular emphasis on, Nigeria, the paper establishes the impacts of the different composite factors of religion, culture, polity, and socio-economy on begging. The paper sees poverty and other socioeconomic factors as central issues in addressing the problem of begging in cities. It identifies or rather, generates certain constructs and hypotheses, which may provide a suitable platform for empirical studies on the phenomenon.